2018
DOI: 10.3390/met8070507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tempering Temperatures on Tensile Properties and Rotary Bending Fatigue Behaviors of 17Cr2Ni2MoVNb Steel

Abstract: Abstract:With the rapid development of the automotive industry in China, the common gear steels no longer meet the high speed and heavy load requirements of the automotive industry. 17Cr2Ni2MoVNb steel is a new type of gear steel in the automotive industry, but the mechanical properties of 17Cr2Ni2MoVNb are not well documented. In this study, the tensile properties and rotary bending fatigue behaviors of 17Cr2Ni2MoVNb were investigated, (quenched at 860 • C and tempered at 180, 400, 620 • C); the microstructur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…Because the addition of the microalloying element Nb hinders the growth of austenite grains during carburizing, the grain size of 17CrNi2MoVNb is relatively fine and uniform [ 16 ]. A small amount of Ni can improve the ductility of alloys, the added Mo is helpful for precipitation strengthening, and a small amount of V can inhibit the abnormal growth of austenite grains [ 17 , 18 ]. Therefore, 17CrNi2MoVNb alloys present the advantages of relatively high surface hardness as well as superior strength and toughness.…”
Section: Experimental Workmentioning
confidence: 99%
“…Because the addition of the microalloying element Nb hinders the growth of austenite grains during carburizing, the grain size of 17CrNi2MoVNb is relatively fine and uniform [ 16 ]. A small amount of Ni can improve the ductility of alloys, the added Mo is helpful for precipitation strengthening, and a small amount of V can inhibit the abnormal growth of austenite grains [ 17 , 18 ]. Therefore, 17CrNi2MoVNb alloys present the advantages of relatively high surface hardness as well as superior strength and toughness.…”
Section: Experimental Workmentioning
confidence: 99%
“…An earlier investigation using 17Cr2Ni2MoVNb gear steel samples tempered at 180 °C, 400 °C, and 620 °C temperatures found that fatigue life rose as cycle stress reduced and decreased as tempering temperatures climbed from 180 °C to 600 °C, which is consistent with the current findings. [18]. It should be emphasized that the dislocation had a role in determining fatigue strength limitations, and high-density dislocations helped to improve fatigue strength.…”
Section: Schemes the Relation Between Maximum Stress And Number Of Cy...mentioning
confidence: 99%
“…While the temperature ranges of phase change are covered in detail [17]. Articles [18][19][20] show that stress behavior in PHS is subject to surface irregularities, such as crack defects in the coating and shear edge defects, which act as the sites of initiation and growth of fatigue cracks. These effects can be reduced by conducting lead-piercing or sandblasting operations that smooth the surface and eliminate internal stresses, as noted in articles [21][22][23] that of uncoated PHS and AHSS.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the higher tempered specimens exhibited a large grain size. 21,32 The average hardness values of specimens are represented in a graph with respect to untempered and tempered temperatures shown in Figure 1(b). The curve is almost straight.…”
Section: Mechanical Propertiesmentioning
confidence: 99%